2015
DOI: 10.4102/sajp.v71i1.286
|View full text |Cite
|
Sign up to set email alerts
|

The role of physiotherapy in the treatment of HIV-related sensory neuropathy: The perceptions and referral practices of physicians

Abstract: BackgroundHIV-related peripheral neuropathies are among the most prevalent chronic neurological disorders affecting persons living with HIV and AIDS. In order to improve the physical function and quality of life of those affected by the disease, a holistic or multidisciplinary approach, including physiotherapy, has been suggested for the management of neuropathic pain.AimThe aim of this study was to explore the physicians’ perceptions regarding the role of physiotherapy in the management of patients with HIV-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
0
0
0
Order By: Relevance
“…14 The findings of this present study may be the major barriers to utilization of physiotherapy services because if physiotherapists had good knowledge in HIV condition and management as reported in other studies, then they would have been prompted to engage in sensitization programs and awareness creation among the HCP and PLWHA which would subsequently boost utilization levels. 15 By so doing, barriers like poor physiotherapist-HCP communication with regards to HIV management, poor recommendation/ referral to physiotherapy services by HCP, poor awareness creation by physiotherapists as identified in this study, would have been counteracted/neutralized. Although, a study identified poor perception of physicians in Tanzania on the role of physiotherapy in HIV associated sensory neuropathy as a barrier to utilization of physiotherapy.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…14 The findings of this present study may be the major barriers to utilization of physiotherapy services because if physiotherapists had good knowledge in HIV condition and management as reported in other studies, then they would have been prompted to engage in sensitization programs and awareness creation among the HCP and PLWHA which would subsequently boost utilization levels. 15 By so doing, barriers like poor physiotherapist-HCP communication with regards to HIV management, poor recommendation/ referral to physiotherapy services by HCP, poor awareness creation by physiotherapists as identified in this study, would have been counteracted/neutralized. Although, a study identified poor perception of physicians in Tanzania on the role of physiotherapy in HIV associated sensory neuropathy as a barrier to utilization of physiotherapy.…”
Section: Discussionmentioning
confidence: 80%
“…This is in agreement with the findings of so many studies regarding the perception of healthcare providers on role of physiotherapy in HIV condition and management. 12,15 Also, the remaining few who were aware of possible roles of physiotherapy obtained this information mainly from doctors and other sources not necessarily physiotherapist (Table 2). This implies that physiotherapist may not have created awareness on their specific role in HIV management or there is poor interdisciplinary team work in HIV management.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation